Introduction to measures of inequality and concentration in tourism - Fernández-Morales, Antonio (My University, 2016)
There are many statistical measures available in the literature for the analysis of inequality and concentration. The most common measure in this field is the Gini index (Roselló Nadal et al.,2004), which is associated to the Lorenz curve. Both were developed at the beginning of the 20th century: the Lorenz curve in 1905 and the Gini index in 1914 (Giorgi,!1993). A revision of recent applications of these measures in the field of tourism can be found in Cisneros Martín and Fernández Morales (2015)and Duro (2016).
Keywords: Desigualdad social; Turismo; Indice de GIni; Curva de Lorenz